CYP24A1 as a Potential Target for Cancer Therapy - Sakaki, Toshiyuki; Yasuda, Kaori; Kittaka, Atsushi; Yamamoto, Keiko; Chen, Tai C. (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Increasing evidence has accumulated to suggest that vitamin D may reduce the risk of cancer through its biologically active metabolite, 1α,25(OH)2D3, which inhibits proliferation and angiogenesis, induces differentiation and apoptosis, and regulates many other cellular functions. Thus, it is plausible to assume that rapid clearance of 1α,25(OH)2D3 by highly expressed CYP24A1 could interrupt the normal physiology of cells and might be one cause of cancer initiation and progression. In fact, enhancement of CYP24A1 expression has been reported in literature for many cancers. Based on these findings, CYP24A1-specific inhibitors and vitamin D analogs which are resistant to CYP24A1-dependent catabolism might be useful for cancer treatment. CYP24A1-specific inhibitor VID400, which is an azole compound, markedly enhanced and prolonged the antiproliferative activity of 1α,25(OH)2D3 in the human keratinocytes. Likewise, CYP24A1-resistant analogs such as 2α-(3-hydroxypropoxy)-1α,25(OH)2D3 (O2C3) and its C2-epimer ED-71 (Eldecalcitol), and 19nor- 2α-(3-hydroxypropyl)-1α,25(OH)2D3 (MART-10) showed potent biological effects. Our in vivo studies using rats revealed that MART-10 had a low calcemic effect, which is a suitable property as an anticancer drug. Much lower affinity of MART-10 for vitamin D binding protein (DBP) as compared with 1α,25(OH)2D3 may be related to its more potent cellular activities. Based on these results, we conclude that (1) high affinity for VDR, (2) resistance to CYP24A1-dependent catabolism, (3) low affinity for DBP, and (4) low calcemic effect may be required for designing potent vitamin D analogs for cancer treatment.
Keywords: CYP24A1